Competencies of E-teaching - Asraa ussain Aliwi / Ahmed Abdul MohsinKhadim ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
One of the most important challenges facing the educational process today is the ability of teachers to discover new educational methods based on knowledge of modern media in order to design an appropriate learning environment for e-learning, and to be creative in its use and investment according to the needs of learners, and this provides continuous progress in the field of technology. Education, due to the circumstances that the whole world is going through as a result of the Covid-19 virus, so the international educational process was subjected to a review in order to keep pace with modern requirements and technologies available for the continuation of education in schools and universities and at all educational levels. The solution is to continue between the teacher and the learner, but the field of e-learning and its solutions will not be successful if it lacks basic factors in some countries and some curricula .E-learning has not achieved many tasks in an indirect or invisible manner for some fields, which sees that e-learning will block the educational process in a deep way. DOI /10.54633/2333-021-042-006